ANALYSIS OF SELECTION OF ARSENAL WAREHOUSE LOCATIONS TO SUPPORT KRI OPERATIONS IN THE KOARMADA II AREA - Muhammad Arif; Avando Bastari; Ahmadi Ahmadi (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
ABSTRACT The global dynamics that are uncertain is one of the main factors affecting the success of achieving the goals and interests in the field of national defense. This reflects how important it is for stakeholders in the defense sector, to understand the dynamics of the strategic environment which presents a series of opportunities, obstacles to threats to the existence of the Republic of Indonesia, which in the end will obtain strategic steps to overcome them. The consideration of the development of the strategic environment that is constantly changing will affect the planning process for the development of the Indonesian Navy, one of which is increasing the operational capability supported by logistical capabilities. In particular, the need for ammunition and weapons that are included in the class V provision to support KRI in an operation. Therefore, it is very necessary to have an Arsenal area warehouse specifically for the Koarmada II region. The speed and accuracy of class V supply support for the KRI elements of the Koarmada II region can be seen from the huge function and role of logistical support, especially in the field of ammunition logistics support distribution, a thought is needed to establish another Arsenal regional warehouse to assist the duties and roles of Arsenal Batu Poron. The choice of location determination has several factors that need to be considered so that it is categorized in a multicriteria decision environment, so the proposed model is the right methodology to accommodate the criteria divided into qualitative and quantitative by using the Fuzzy MCDM (Multi Criteria Decision Maker) approach. Qualitative criteria for selecting the best warehouse location in Arsenal area include security criteria, transportation access, and warehouse support facilities, while quantitative criteria include distance to enemies, distance to settlements and earthquake factors that affect the construction of Arsenal area warehouses. In this study, from five alternative locations, namely Lantamal V Surabaya, Lantamal VI Makassar, Lantamal VII Kupang, Lantamal VIII Manado and Lantamal XIII Tarakan. Keywords: Strategic Environment, Arsenal area warehouse, Fuzzy MCDM, facility design.